Severe bacterial skin infections, - Sílvio Alencar Marques; Luciana Patrícia Fernandes Abbade (Sociedade Brasileira de Dermatologia, 2020)
Abstract The severe bacterial diseases discussed herein are those that present dermatological lesions as their initial manifestations, for which the dermatologist is often called upon to give an opinion or is even the first to examine the patient. This review focuses on those that evolve with skin necrosis during their natural history, that is, necrotizing fasciitis, Fournier gangrene, and ecthyma gangrenosum. Notice that the more descriptive terminology was adopted; each disease was individualized, rather than being referred by the generic term "necrotizing soft tissue infections". Due to their relevance and increasing frequency, infections by methicillin-resistant Staphylococcus aureus (MRSA) were also included, more specifically abscesses, furuncle, and carbuncle, and their potential etiologies by MRSA. This article focuses on the epidemiology, clinical dermatological manifestations, methods of diagnosis, and treatment of each of the diseases mentioned.